Advance selling in the wake of entry - Nadia Ceschi; Marc Möller (University of Bern, Department of Economics, 2021)
This article provides a tractable model of inter-temporal price-discrimination by heterogeneous firms, imperative for our understanding of advance purchase markets in the wake of entry. The pricing schedule of a more efficient entrant is found to differ systematically from the pricing schedule of a more prominent incumbent. By diverting competition to a stage where consumers face uncertainty about their preferences, advance selling reduces prices while increasing the entrant's market share and profitability relative to the incumbent. Policies that curtail the firms' ability to sell in advance, although potentially beneficial for welfare, may have the adverse effects of consolidating an incumbent's position and of reducing the consumers' surplus.
Keywords: D43; D80; L13; 330; Competition; Price Discrimination; Individual Demand Uncertainty; Advance Purchase Discounts